La Gran Logia Bonaerense y su preocupación por la educación: Una de las fuentes del rito nacional español - Darrigran Algaba, Gabriel (2017)
The main purpose of this text is an initial approach to the educational project of a little-known argentine masonic society, which arose in the 19 th century, and was highly influenced by the Scientific Positivism. The Grand Lodge of Buenos Aires, one of the results of a city planned to be a “Model City”, which sought to be considered since its beginnings an Institute of Higher Learning, educating the working class and the lower middle class. Furthermore, we show, through the Atlantic Masonic Networks, how its doctrines succeeded in influencing Spain and changing part of the structure of the Symbolic Grand Lodge of Spain and therefore, is considered to be one of the sources of the Iberian Grand Orient Rite.